Pengaruh Aromaterapi Tea Tree Oil Pada Anak Dengan ISPA - Siska Afrilya Diartin; Syeptri Agiani Putri (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
ARI is an infectious disease that attacks one or more parts of the respiratory tract, starting from the nose (upper tract) to the alveoli (lower tract) including adnexal tissue, such as the sinuses, middle ear cavity and pleura. ISPA is a respiratory tract infection that lasts for 14 days. ARI can be caused by various causes such as bacteria, viruses, fungi and aspiration. Bacteria that cause ARI include Diplococcus Pneumoniae, Pneumococcus, Streptococcus Pyogenes Staphylococcus Aureus, Haemophilus Influenza, and others. Viruses that cause ARI include influenza, adenovirus, cytomegalovirus. Fungi that cause ARI include Aspergillus Sp, Candida Albicans Histoplasm, and others. Apart from being caused by bacteria, viruses and fungi, ISPA is also caused by aspiration such as food, motor vehicle fumes, fuel oil, amniotic fluid at birth, foreign objects (seeds), small plastic toys, and others. The occurrence of ISPA is certainly influenced by many factors, namely environmental conditions (air pollutants such as cigarette smoke and cooking fuel fumes, density of family members, house ventilation conditions, humidity, cleanliness, season, temperature), availability and effectiveness of health services and infection prevention measures. to prevent spread (vaccines, access to health care facilities, isolation room capacity), host factors (age, smoking habits, ability of the host to transmit infection, nutritional status, previous infections or simultaneous infections caused by other pathogens, general health conditions) and characteristics pathogen (mode of transmission, infectivity, virulence factors such as genes, number or dose of microbes).